A world of three zeros the new economics of zero poverty, zero unemployment, and zero net carbon emissions - Yunus, Muhammad 1940-; Weber, Karl 1953- (PublicAffairs, 2017)
Muhammad Yunus, who created microcredit, invented social business, and earned a Nobel Peace Prize for his work in alleviating poverty, is one of today's most trenchant social critics. Now he declares it's time to admit that the capitalist engine is broken--that in its current form it inevitably leads to rampant inequality, massive unemployment, and environmental destruction